Prediction of equilibrium products and thermodynamic properties in H2O injected combustion for CαHβOγNδ type fuels - Kayadelen, Hasan Kayhan; Ust, Yasin (ELSEVIER SCI LTD, 2013)
Water and steam injection at the upstream or in the combustion chamber or using fuel-water emulsions are both well proven methods for reducing NOx emissions and improving performance of many types of internal combustion engines. This study involves a thermodynamic simulation of water/steam injected combustion which can be used with any C alpha H beta O gamma N delta type fuel and for any combustion engine. The simulation determines the mole fractions of each exhaust species at chemical equilibrium according to equilibrium-constant approach and then thermodynamic properties of the exhaust gas mixture. Previous studies about steam/water injected power systems concentrate on some particular exhaust species such as CO and NOx and unable to predict the thermodynamic properties of working fluid accurately which is needed for an accurate performance estimation. According to previous researchers, thermodynamic properties calculated with this approach depending on the equilibrium composition are precise and can directly be used for performance estimation of combustion engines. The model gives equilibrium mole fractions, specific heat of the exhaust mixtures and adiabatic flame temperatures and results for four different fuels and varying steam/water injection ratios are presented. Apart from being directly applicable to steam/water injected power systems, the modeling process is described elaborately in order to make it adaptable for future studies such as multi-fuel or EGR applications for any desired number of exhaust species. Additionally, the equilibrium composition obtained, can also be used for determination of non-equilibrium pollutant values using existing chemical kinetics correlations in the literature. This approach provides the basic needs for the two key objectives of engine design; performance evaluation and emission optimization'' by providing an accurate method for steam/water injected power systems. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Emissions; Water emulsion; Water injection; Steam injection; Chemical equilibrium; POLLUTANT EMISSIONS; DIESEL; ENGINE; PERFORMANCE; SIMULATION; Energy & Fuels; Engineering